Diskursus Al-Qur’an dan Prosesi Pewahyuan - Muhamad Yoga Firdaus; Izzah Faizah Siti Rusydati Khaerani; Hanna Salsabila (Madania: Jurnal Ilmu-Ilmu Keislaman, 2022)
The goal of this study is to delve into the Al-Qur'an and the manner through which it was revealed. This brief study is qualitative in nature and is based on a survey of the literature. The analysis was then carried out using content analysis techniques and an interpretation methodology. This study's findings and discussions include the theme of revelation and the Qur'an, the procession of the revelation of the Al-Qur'an, and the gradation of perceptions related to the revelation of the Al-Qur'an. The revelation, as well as the revelation procession, served as a precursor to the critical 'Ulum al-Qur'an debate. The diverse perspectives on the revelation procession become the ideal bridge for lovers of knowledge of the Al-Qur'an in investigating the innermost meaning of the entity of the Al-Qur'an so that it may also be accepted and understood by the general population, wherever and whenever they are. Particularly for Muslims who are guided by the Al-Qur'an. This modest study has limitations, especially the absence of determination of new perceptions, so that they continue to analyze already existing information, resulting in information that is confined to reinforcing and enhancing knowledge about the revelation process. This modest study also suggests that in the future, fresh viewpoints on the process of the revelation of the Al-Qur'an may be discovered.